2012
DOI: 10.1134/s0026893312020124
|View full text |Cite
|
Sign up to set email alerts
|

Association of chromosome 8q24 variants with prostate cancer risk in the Siberian region of Russia and meta-analysis

Abstract: Compelling evidence demonstrates the importance of chromosome 8q24 as a locus of susceptibil ity to prostate cancer. In this work, the association of common 8q24 variants, rs6983267 and rs1447295, with a sporadic risk of prostate cancer was analyzed in the Russian population of Siberia. For this purpose, the above polymorphisms were genotyped in 393 cases and 384 control individuals. The A allele of rs1447295 was significantly associated with prostate cancer risk (OR[CI 95%] = 1.74 [1.26-2.4], p = 7.8 × 10 -4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…In 2006, Amundadottir et al found in Iceland, Sweden, and other populations that multiple SNPs in the chromosome 8q24 region are closely related to the risk of prostate cancer (PCa) by a large genome-wide association study (GWAS) (3). This correlation has been followed and confirmed in European Americans, African Americans and native Hawaiians, Spain, the Netherlands, Japan, and other peoples (4)(5)(6)(7)(8)(9)(10)(11). China has a few studies on the correlation between 8q24 region and PCa (12,13), but the results are not completely consistent.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Amundadottir et al found in Iceland, Sweden, and other populations that multiple SNPs in the chromosome 8q24 region are closely related to the risk of prostate cancer (PCa) by a large genome-wide association study (GWAS) (3). This correlation has been followed and confirmed in European Americans, African Americans and native Hawaiians, Spain, the Netherlands, Japan, and other peoples (4)(5)(6)(7)(8)(9)(10)(11). China has a few studies on the correlation between 8q24 region and PCa (12,13), but the results are not completely consistent.…”
Section: Introductionmentioning
confidence: 99%